Clinic aspects of osteoporotic children and adolescents - Şen, Yaşar; Yeşilkaya, Ediz; Atçi, Bekir; Özkan, Esin; Akarsu, Saadet (My University, 2008)
Objective: There is no enough data about childhood osteoporosis in our country. Data about osteoporosis are taken from adult patients and case reports. The present study was designed to determine clinic aspects of osteoporosis in children and adolescents. Materials and Methods: Files of patients who had osteoporosis diagnosis were reviewed retrospectively and clinic aspects were determined. Patients were diagnosed as osteoporosis if a BMD, which was measured by Lunar DPX-IQ (DEXA), was low related to age and gender and Z score was below 2SD, additionally to clinical signs. Results: Among patients followed by our pediatric endocrinology polyclinic, osteoporosis frequency was found as 1,1% (n=40). Of the 40 cases with osteoporosis, 17 were female, 23 were male and mean age was 13,4 ±3,7 years. aBMD of patients was 0,68 ±0,18 gr/cm2 (0,27-1,07) and BMP Z score was -3,1 ±1,1. There was no significant difference between males and females regarding the BMD, Z score and biochemical markers (p>0,05). It was seen that patients with secondary osteoporosis were more than patients with primary osteoporosis (n=32, 80%) and that mostly endocrinologic diseases caused secondary osteoporosis (n=12, 30%). Oral Ca and vitamin D were given to 28 cases (70%), i.v. biphosphonate to 4 cases (10%), and intranasal calcitonin was given to 3 cases (7,5%) as treatment. Conclusions: Among our osteoporosis patients, secondary osteoporosis was shown to be seen more often. Besides, it was detected that if there was no recurrent fractures, osteoporosis could be overlooked and that these patients generally had diagnosis lately. Especially for children and adolescents who has osteoporosis risk factors, early diagnosis and treatment have great importance for bone health in their future adult life. Copyright © 2008 by Türk Tibbi Rehabilitasyon Kurumu Derne?i.
Osteoporozlu çocuk ve ergenlerin klinik özellikleri
Keywords: Adolescents; Children; Osteoporosis; Treatment